Examining the Energy-Growth Dynamics in Saudi Arabia: Insights and Policy Implications - Haque, Mohammad Imdadul; Tausif, Mohammad Rumzi (International Journal of Energy Economics and Policy, 2024)
The empirical relationship between energy consumption and economic growth is complex and varies by country and model specification. This study focuses on Saudi Arabia, one of the largest producers and exporters of crude oil, to explore this relationship. Our analysis refutes the Energy-Kuznets Curve hypothesis for Saudi Arabia, finding neither a linear nor a curvilinear relationship between economic growth and energy consumption. Instead, we observe an asymmetric impact of economic growth on energy consumption: the rate of increase in energy consumption with rising per capita income differs from the rate of decrease when per capita income falls. Additionally, the study reveals a positive impact of investment on energy consumption, indicating a dynamic interplay between economic growth, industrial activity, and improved energy access. These findings suggest that energy consumption patterns in Saudi Arabia are intricately linked to economic fluctuations but are not uniformly predictable. Policy recommendations are provided to address these complexities and promote sustainable growth.